1996
DOI: 10.1063/1.117351
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling current noise in thin gate oxides

Abstract: We have examined fluctuations in the tunneling current of 3.5 nm SiO2 barriers for voltages in the direct tunneling regime. We find a 1/f power law for the spectral density of the fluctuations where f is the frequency. This 1/f noise can be attributed to fluctuations of a trap assisted tunneling current through the oxide that causes current noise but is not evident in the I–V curves. We suggest that this noise may be a more sensitive probe of trap assisted tunneling and degradation in thin oxides than other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…For higher currents, an dependence is observed with and is explained by the influence of the Schottky barrier's series resistance. Assuming that the LF barrier height fluctuations are caused by trap assisted tunnelling, in analogy with the case of thin silicon oxides [12], we interpret this significant reduction in LF gate current noise as being caused by a strong reduction of the density (or trap parameters) of the effective tunnelling defects. At the same time, the lower ideality factor of the 60% Al containing structure in the Schottky layer also contributes to the reduction of the LF gate current noise.…”
Section: Resultsmentioning
confidence: 99%
“…For higher currents, an dependence is observed with and is explained by the influence of the Schottky barrier's series resistance. Assuming that the LF barrier height fluctuations are caused by trap assisted tunnelling, in analogy with the case of thin silicon oxides [12], we interpret this significant reduction in LF gate current noise as being caused by a strong reduction of the density (or trap parameters) of the effective tunnelling defects. At the same time, the lower ideality factor of the 60% Al containing structure in the Schottky layer also contributes to the reduction of the LF gate current noise.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have observed noise in the gate current [48]- [50]. Alers [48] has attributed this to the phenomenon of trap-assisted tunneling.…”
Section: Noise Of the Gate Currentmentioning
confidence: 99%
“…Thus simple molecular adsorption does not appear to provide a complete explanation for the change in emission. Very similar fluctuations also occur in solid-state devices (e.g., MOS structures) where adsorption cannot occur, and have been explained as changes in interface (oxide) charge [77].…”
Section: Fluctuationsmentioning
confidence: 90%